KOMUNIKASI PEMASARAN TERPADU DALAM MENGEMBANGKAN CITRA SSB PANDANARAN BOYOLALI - Febriyanto, Puput (The Commercium, 2025)
In football, building an image is an important thing to do to achieve good growth and long-term, lasting success. For this reason, this research was conducted to determine the role of integrated marketing communication strategies as well as the challenges and obstacles faced by the SSB Pandanaran Boyolali management. This research uses a qualitative descriptive method, with the research subjects being the management, the students, the parents, and the people in Boyolali. The data was collected using observation, interviews, and documentation techniques. The research shows that 1) integrated marketing communications have a role in conveying information about the existence of SSB Pandanaran Boyolali. 2) the integrated marketing communications strategy carried out by SSB Pandanaran Boyolali through a promotion mix, namely advertising, direct marketing, personal sales, internet marketing, and public relations. 3) lack of awareness of payments is an obstacle for the SSB Pandanaran Boyolali management. 4) The football culture in Boyolali could be more assertive, making it a challenge for the management to get many people to follow and join SSB Pandanaran Boyolali. The research concludes that the integrated marketing communication strategy carried out by SSB Pandanaran has been going properly.